Chronic uranium exposure dose-dependently induces glutathione in rats without any nephrotoxicity. (October 2014) - Poisson, C.; Stefani, J.; Manens, L.; Delissen, O.; Suhard, D.; Tessier, C.; Dublineau, I.; Guéguen, Y.
Abstract Uranium is a heavy metal naturally found in the earth's crust that can contaminate the general public population when ingested. The acute effect and notably the uranium nephrotoxicity are well known but knowledge about the effect of chronic uranium exposure is less clear. In a dose-response study we sought to determine if a chronic exposure to uranium is toxic to the kidneys and the liver, and what the anti-oxidative system plays in these effects. Rats were contaminated for 3 or 9 months by uranium in drinking water at different concentrations (0, 1, 40, 120, 400, or 600 mg/L). Uranium tissue content in the liver, kidneys, and bones was linear and proportional to uranium intake after 3 and 9 months of contamination; it reached 6 μg per gram of kidney tissues for the highest uranium level in drinking water. Nevertheless, no histological lesions of the kidney were observed, nor any modification of kidney biomarkers such as creatinine or KIM-1. After 9 months of contamination at and above the 120-mg/L concentration of uranium, lipid peroxidation levels decreased in plasma, liver, and kidneys. Glutathione concentration increased in the liver for the 600-mg/L group, in the kidney it increased dose dependently, up to 10-fold, after 9 months of contamination. Conversely, chronic uranium exposure irregularly modified gene expression of antioxidant enzymes and activities in the liver and kidneys. In conclusion, chronic uranium exposure did not induce nephrotoxic effects under our experimental conditions, but instead reinforced the antioxidant system, especially by increasing glutathione levels in the kidneys.